Evaluation of the transcriptional status of host cytokines and viral genes in the trachea of vaccinated and non-vaccinated chickens after challenge with the infectious laryngotracheitis virus. Issue 1 (2nd January 2016) - Vagnozzi, Ariel; Riblet, Sylva; Zavala, Guillermo; Ecco, Roselene; Afonso, Claudio L.; García, Maricarmen
ABSTRACT: Infectious laryngotracheitis is a highly contagious disease of chickens responsible for significant economic losses for the poultry industry worldwide. The disease is caused by Gallid herpesvirus-1 (GaHV-1) commonly known as the infectious laryngotracheitis virus. Although characterized by their potential to regain virulence, chicken embryo origin (CEO) vaccines are the most effective vaccines against laryngotracheitis as they significantly reduce the replication of challenge virus in the trachea and conjunctiva. Knowledge on the nature of protective immunity elicited by CEO vaccines is very limited. Therefore, elucidating the origin of the immune responses elicited by CEO vaccination is relevant for development of safer control strategies. In this study the transcription levels of key host immune genes (IFN-γ, IFN-β, IL-1β, IL-6, IL-8, IL-18) and viral genes (ICP4, ICP27, UL46, UL49), as well as viral genome loads in trachea were quantified at 6 and 12 hours post-challenge of CEO vaccinated and non-vaccinated chickens. Immediately after challenge a significant increase in IFN-γ gene expression was followed by a significant reduction in viral replication. In contrast to the rapid induction of IFN-γ, expression of the pro-inflammatory cytokines (IL-1β, IL-6, IL-8) and type I IFN β was either slightly reduced or remained at basal levels. These suggest that the former cytokines may not play important roles during immediate early responses induced by ILTV challenge in either vaccinated or non-vaccinated chickens. Overall, these results suggest that the rapid expression of IFN-γ may induce pathways of antiviral responses necessary for blocking early virus replication.